Relevansi Landasan-landasan dan Sumber Pendidikan Islam di Era Society 5.o - Nur Muhammad Khoirul Umam; Anisah Fitri Melenia; Ahmad Hikam Mutha'aliin; Hasan Basri; Mauzifa (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the relevance of the foundations and sources of Islamic education in responding to the dynamics of the Society 5.0 era. This research employs a qualitative approach through library research by examining various scholarly works related to Islamic education, digital transformation, and twenty-first century educational frameworks. The findings reveal that the philosophical, sociological, cultural, and psychological foundations of Islamic education remain essential in shaping its direction, despite rapid technological and social changes. These foundations function as guiding principles to maintain the values, character formation, and core objectives of Islamic education in the digital age. Moreover, the Qur’an and Sunnah as the primary sources of Islamic education continue to serve as fundamental references for moral guidance and ethical use of technology. The integration of Islamic values with technological advancements enables more adaptive, effective, and meaningful learning processes. Overall, this study affirms that Islamic education possesses the flexibility to adapt to the demands of the Society 5.0 era without losing its essential identity, and it holds a strategic role in shaping digitally literate, ethical, and competent Muslim generations capable of navigating contemporary global challenges.